Towards Meaningful University Space: Perceptions of the Quality of Open Spaces for Students - Saba Alnusairat (MDPI AG, 2021)
This study investigated students’ attitudes towards the use of outdoor open space in universities, identifying the most comfortable conditions and favourable factors, including urban layout, physical features, and outdoor thermal conditions, as well as the students’ needs and behaviour. A quasi-experiment was used to assess the quality of the outdoor spaces. Three outdoor open spaces on the university’s campus were used for the case study. A spatial analysis employing space syntax was used to determine the integration, agent, and connection factors. For the microclimate conditions, simulations were conducted. The students’ actions were recorded, and a questionnaire concerning their preferences was disseminated. According to the respondents, the key advantages of campus open spaces are that they provide places in which to socialise and rest and to pass by. The data revealed a correlation between microclimate conditions and the use of outdoor spaces. However, the students use outdoor venues even in unfavourable microclimates. The visual factor and spatial configuration of the site have a significant impact on the use of open spaces; hence, visibility is an important feature in campus layouts. This study established a baseline of data to integrate social and contextual factors for the creation of meaningful spaces in universities.